Commitment and responsibility in nursing: a faith-based approach - Cusveller, B. S. (Dordt College Press, 2004)
What is professional responsibility in nursing practice? / Bart Cusveller -- Changing perceptions of nurses' professional responsibility and lessons from history / Ann Bradshaw -- Communicating Christian conviction / Arlene B. Miller -- Professional responsibility in the patient-nurse relationship / Kees Kleingeld -- Professional responsibility in nurses' relationships to colleagues and their profession / Fu-Jin Shih -- Professional responsibility in interdisciplinary health care teams and cooperative working relationships / Jan van der Wolf -- Professional responsibility at the end of life / Ada van Bruchem-Van de Scheur -- Professional responsibility concerning alternative therapies / Dónal P. O'Mathúna -- Professional responsibility concerning intimacy and sexuality in patient care / Bart Cusveller and Dónal P. O'Mathúna.